(SOFXA XJ DP]VJs - Russell Bertrand ((SL(B.(SE(B. (SAuvfplejw (B& (SVlga(B,s, 1963)
(SXL SLVXFY] FSLIRYOF XRY KAPAXRY(B; (SSPFYOAXLMA ASRUULOOAXA VY[URPJ VMF\J DLAXL EFP FLOAL [ULVXLAPRVs
(SXL SLVXFY] FSLIRYOF XRY KAPAXRY(B; (SSPFYOAXLMA ASRUULOOAXA VY[URPJ VMF\J DLAXL EFP FLOAL [ULVXLAPRVs